Atomic scale imaging of competing polar states in a Ruddlesden–Popper layered oxide - Greg Stone (Nature Portfolio, 2016)
Competing phases in layered complex oxides are believed to be relevant for emergent phenomena, which still await to be witnessed. Here, Stone et al. report direct atomic-scale imaging of a multitude of polar phases in Ruddlesden-Popper oxide thin films, exhibiting diverse phenomena in a single structure.